The Farjam Collection: From Matisse to Warhol- Works on Paper by Modern Masters (3eLehYI aQLGe(B: (3ef eGJjS Edi hGQghd(B- (3CYeGd Ydi GdhQb dCSGJPI GdMOGKI s - Farjam Collection (Dubai; The Hafiz Foundation, 2010)
For its third exhibition, The Farjam Foundation departs from its former displays of Islamic art to present a fascinatingly varied display of drawings which covers 70 years of modern Western art. Encompassing works on paper by some of the most respected artists of the twentieth century, this exhibition shows fine examples of what is arguably the most direct form of creative expression.
English
Keywords: N5198-5299 Visual Arts- Private collections and collectors